Treinamento aeróbio e diabetes experimental em ratos: perfil endócrino-metabólico no cerebelo - Arantes, Luciana Mendonça [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This study had been designed to evaluate the aerobic exercise training effects on endocrine- metabolic profile of diabetic rats, with greater emphasis in the cerebellum. Therefore, adult Wistar rats had been submitted to induction by injecting alloxan monohydrate. Five days after the drug administration, a blood glucose test was performed for proving the glucose diabetic state of the animals, being considered diabetic only those rats which had shown blood glucose equal or higher than 250 mg per 100 ml of blood. After the finding of diabetes, the rats were divided randomly into four groups: Sedentary Control (SC) - control rats which did not engage in physical exercise; Trained Control (TC) - control rats which were submitted to the physical exercise protocol; Sedentary Diabetic (SD) - alloxan diabetic rats which were not submitted to the physical exercise protocol; Trained Diabetic (TD) - alloxan diabetic rats that were submitted to the same physical exercise protocol group of the trained control group (TC). The physical exercise training protocol had been consisted of swimming for 1 hour / day, 5 times / week during 8 consecutive weeks and with an overload, attached to the chest, corresponding to the maximum lactate steady state, in % of the body weight. The values of the blood glucose and triglycerides were increased in diabetic animals (SD and TD) and both were reduced in the trained diabetic group when compared to the sedentary diabetic group values. The inducing of diabetes reduced the insulin values in the animals of both groups (SD and TD), and the physical exercise training has not changed the values of this parameter. The aerobic training did not affect the concentrations of IGF-1 and insulin in the cerebellum. Differences had been observed in the body balance of the diabetic rats and control group. The diabetic group had shown lower performance than the control group, presenting greater difficulty in the activities that require...

O presente estudo foi delineado para avaliar os efeitos do treinamento físico aeróbio no perfil endócrino-metabólico de ratos diabéticos, com maior ênfase no tecido cerebelar. Para tanto, ratos adultos da linhagem Wistar foram submetidos à aplicação com aloxana monoidratada Sigma (32 mg/kg de peso corporal). Cinco dias após a administração da droga, será realizado um teste de glicemia para comprovação do estado diabético dos animais, sendo considerados diabéticos apenas aqueles ratos que apresentarem glicemia igual ou superior a 250 mg por 100 ml de sangue. Após a constatação do diabetes, os ratos foram distribuídos, aleatoriamente, em quatro grupos: Controle Sedentário (CS) - ratos controles que não realizarão exercícios físicos; Controle Treinado (CT)- ratos controles que serão submetidos ao protocolo de exercícios físicos; Diabéticos Sedentários (DS) - ratos diabéticos aloxânicos que não serão submetidos ao protocolo de exercícios físicos; Diabéticos Treinados (DT) - ratos diabéticos aloxânicos que serão submetidos ao mesmo protocolo de exercícios físicos do grupo controle treinado (CT). O protocolo de treinamento físico consistirá de natação por 1 hora/dia, 5 vezes/semana, durante 8 semanas consecutivas e com sobrecarga, atada ao tórax, correspondente à máxima fase estável de lactato, em % do peso corporal. Os valores de glicemia e trigliceridemia foram aumentados nos animais diabéticos (DS e DT) e ambos foram reduzidos no grupo diabético treinado quando comparados aos valores do grupo diabético sedentário. A indução do diabetes reduziu os valores de insulinemia nos animais de ambos os grupos (DS e DT) e o treinamento físico não alterou os valores deste parâmetro. O treinamento aeróbio não modifica as concentrações de IGF-1 e Insulina no cerebelo. Foi observado diferenças no equilíbrio corporal de ratos diabéticos e controles. O grupo diabético apresentou menor desempenho que.
Keywords: Sports medicine; Medicina esportiva; Glicemia; Morfologia (Animais); Cerebelo; Insulina; Exercícios aeróbicos; Fisiologia; Diabetes